2015
DOI: 10.1177/1971400915589692
|View full text |Cite
|
Sign up to set email alerts
|

The clinical characteristics and treatment of cerebral AVM in pregnancy

Abstract: Cerebral arteriovenous malformation (AVM) in pregnancy is a complex situation and there is no agreement on its hemorrhage risk and treatment. Although studies on bleeding risk of cerebral AVMs in pregnancy are very few, and they provide different results, pregnancy will increase the hemorrhagic risk of AVM and ruptured cerebral AVM in pregnancy should be actively treated. After intracranial hemorrhage, cerebral angiography should be performed for pregnant women shielded correctly. Cerebral angiography could cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…According to Liu et al the rate of ICH related to cerebrovascular malformations is similar in pregnant and non-pregnant women and that pregnancy does not increase the rate of first cerebral haemorrhage from an AVM [5] . However, other authors have shown an increased risk of AVM rupture during pregnancy [3] . There is a 2-3% annual risk of ICH with AVMs.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…According to Liu et al the rate of ICH related to cerebrovascular malformations is similar in pregnant and non-pregnant women and that pregnancy does not increase the rate of first cerebral haemorrhage from an AVM [5] . However, other authors have shown an increased risk of AVM rupture during pregnancy [3] . There is a 2-3% annual risk of ICH with AVMs.…”
Section: Discussionmentioning
confidence: 84%
“…Amias et al showed a bias in favour of caesarean section in 30 cases when neurological management was conservative [7] . Caesarean section could be a better option as vaginal delivery could precipitate Valsalvamanauver thus precipitate rupture of AVM [2,3,5] . Close collaboration with a team of neurologists, neurosurgeons, obstetricians and anaesthesiologists is mandatory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicate that different strategies are needed for pregnancies complicated with intracranial AVM. In the group where the diagnosis had been made at conception, two cases had risk factors for bleeding, such as coexisting aneurysm, smooth venous drainage, venous ectasia or pregnancy induced hypertension (PIH), so these cases were delivered by cesarean section, and vaginal delivery was attempted for other cases using epidural anesthesia. The results provide evidence that this delivery mode is viable in a pregnancy with unruptured cerebral AVM if the above characteristics are absent on MRA/angiography and there is no hypertensive disorder or coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…uzimajući u obzir literaturne podatke i klinički status bolesnice, odlučili smo da se carski rez izvede u epiduralnoj anesteziji jer smo procijenili da je rizik od rupture avM-a niži nego u općoj anesteziji. [1][2][3]15,18 Možemo zaključiti da naš prikaz potvrđuje kako carski rez može biti uspješno izveden kod bolesnice s avM-om v. stupnja.…”
Section: Raspravaunclassified